180k views
5 votes
Pleases someone explain

Pleases someone explain-example-1

1 Answer

7 votes

When you have a negative exponent, you move the base with the negative exponent to the other side of the fraction to make the exponent positive.

For example:


(1)/(y^(-2)) =(y^2)/(1) or
y^2


2x^(-3) or
(2^1x^(-3))/(1) =(2)/(x^3)


(1)/(x^(-5)) =x^5

When a base with an exponent is divided by a base with an exponent, you subtract the exponents together. (But you can only combine the exponents when the bases are the same)

For example:


(x^2)/(y) (can't combine because they have different bases of y and x)


(x^5)/(x^3) =x^((5-3))=x^2


(2^2)/(2) =2^((2-1))=2^1 = 2

When you multiply an exponent directly to a base with an exponent, you multiply the exponents together.

For example:


(x^2)^3=x^((2*3))=x^6


(y^2)^(10)=y^((2*10))=y^(20)


(2e^0)/((e^(-3))^2) First multiply the exponents together in the denominator


(2e^0)/(e^((-3*2)))= (2e^0)/(e^(-6)) Now subtract the exponents together


2e^((0-(-6))) (two negative signs cancel each other out and become positive)


2e^((0+6))


2e^6

User Dima Patserkovskyi
by
5.5k points